PENGARUH TEKNIK COGNITIVE RESTRUCTURING TERHADAP PENURUNAN PROKRASTINASI AKADEMIK SISWA MELALUI BIMBINGAN KELOMPOK DI SMK KESEHATAN PRO-SKILL INDONESIA PEKANBARU - Rika Putri Handayani; Rosmawati Rosmawati; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of cognitive restructuring techniques on the decline in academic procrastination of students at the Vocational High School Health Pro-Skill Indonesian Pekanbaru. This type of research is quantitative research with the experimental method using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study was the scale of student academic procrastination measurement which consisted of 47 items before validation, and after validation obtained 34 valid items with validity 0.509 and reliability 0.929. The subjects of this study were 7 students who were identified as having high levels of academic procrastination. The data analysis technique used is non parametric statistical techniques using the Rank Spearman test. The results of the study prove that the research hypothesis is accepted. Therefore, from the results of the Rank Spearman test, r = 0.793, while the correlation coefficient r2 is 0.628. Thus there is the influence of cognitive restructuring techniques on student academic procrastination by 63% in Vocational High School Health Pro-Skill Indonesian Pekanbaru. From the results of the Wilcoxon test obtained (Asymp.Sig) 0.018 <0.05 it can be concluded that there are differences in the scores of student academic procrastination before and after cognitive restructuring techniques are given.Key Words: Cognitive Restructuring, Academic Procrastination